Experience of Faith as an Extracting of Good - Grzegorczyk, Anna (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
Biblical, evangelical, philosophical and poetical references to “dwelling of the good” in history of a man reinforce a main argumentation of this article according to which experience of Christian faith has an effective impact to extracting of the good itself.Evangelical narrative and a person of Jesus Christ – according to many philosophers, thinkers and poets, sometimes far from being a believers – are an authentic roots of European civilization, so we have to “protect the good”, that is carried by the words of Gospel and a person of Saviour, and include it into our daily practices. Christianity without its evangelical source, without the foundation of good becomes a mere intellectual matter, as well as European culture without Christianity becomes a “waste land".